Teachers’ Challenges and Students’ Response to Project-Based Learning in English Subject - Winarno (University of Surakarta, 2023)
ABSTRACT This study was conducted to (1) describe project-based learning in the English subject at the vocational high school (SMK Kesehatan Kaltara); (2) describe the challenges or difficulties English teachers encountered in implementing project-based learning in the English subject at the vocational high school (SMK Kesehatan Kaltara); and (3) reveal the students’ responses on PjBL implementation. This study applied a mixed method (Creswell, 2014). The data were collected with observation, questionnaires, and interviews. Then, they were analyzed using the Miles and Huberman formula, including data reduction, data display, and conclusions: drawing/verifying. Based on the analysis, the findings indicate that: (1) English teachers at the school had successfully implemented project-based learning; and (2) the teachers found some following problems: lack of time, learning resources and tools in preparation, difficulty in distributing the whole topic for different groups, time limitation in the class, difficulty in monitoring the activities of the groups and their members, (3) in general the students have positive responses on all learning aspects.